Pieris_napi_linkage_map_removed_markers.tsv - Ramprasad Neethiraj (Stockholm University, 2018)
Collections of scripts and data used in the article "Holocentric chromosomes facilitate high rates of recombination and genetic variation in Lepidoptera "

* List of markers not used in the analysis: "Pieris_napi_linkage_map_removed_markers.tsv" (n=261)
Keywords: 60411 Population, Ecological and Evolutionary Genetics; Biological Sciences; Biologi